A new genus and species of Pleidae (Hemiptera) from Venezuela, with notes on the genera of Pleidae - Cook, Jerry L. (Zootaxa, 2011)
A new genus and species of Pleidae, Heteroplea stictosoma is described from Venezuela. The new genus Heteroplea differs from other genera in having a distinct callus on the occiput and an ovipositor without spines, as well has having a variable medial sternal carina. The genus resembles Plea in having three tarsomeres on each leg but appears closer to Neoplea in many other characters. This species was collected from a hydropetric habitat, which is different than other pleid species normally inhabit. With the addition of this new genus, an updated key to the genera of Pleidae is provided.